Endometriosis with dyspnea - is it possible? - Joanna Knap; Monika Klimek; Marta Masternak; Mateusz Reda (Kazimierz Wielki University, 2019)
Dyspnea is defined by American Thoracic Society as a subjective experience of breathing discomfort that consist of qualitatively distinct sensation that vary in intensity. As a pulmonary symptom, it is rarely associated with pathology of the reproductive organs. However, shortness of breath can be the first sign of endometriosis. The entity known as thoracic endometriosis syndrome is a manifestation of endometriosis, within the lung parenchyma or on the diaphram and pleural surface. This includes catamenial pneumothorax, hemothorax, hemoptysis, and pulmonary nodules.